30% land conservation and climate action reduces tropical extinction risk by more than 50%. Issue 7 (25th February 2020) - Hannah, Lee; Roehrdanz, Patrick R.; Marquet, Pablo A.; Enquist, Brian J.; Midgley, Guy; Foden, Wendy; Lovett, Jon C.; Corlett, Richard T.; Corcoran, Derek; Butchart, Stuart H. M.; Boyle, Brad; Feng, Xiao; et al.
Abstract : Limiting climate change to less than 2°C is the focus of international policy under the climate convention (UNFCCC), and is essential to preventing extinctions, a focus of the Convention on Biological Diversity (CBD). The post‐2020 biodiversity framework drafted by the CBD proposes conserving 30% of both land and oceans by 2030. However, the combined impact on extinction risk of species from limiting climate change and increasing the extent of protected and conserved areas has not been assessed. Here we create conservation spatial plans to minimize extinction risk in the tropics using data on 289 219 species and modeling two future greenhouse gas concentration pathways (RCP2.6 and 8.5) while varying the extent of terrestrial protected land and conserved areas from <17% to 50%. We find that limiting climate change to 2°C and conserving 30% of terrestrial area could more than halve aggregate extinction risk compared with uncontrolled climate change and no increase in conserved area.